Department chairs and interpersonal conflict: a narrative inquiry - Ayers, Audrey Evelyn (Kansas State University, 2023)
Conflict is inevitable in every part of life and institutions of higher education are not immune to experiencing interpersonal conflict. Department chairs hold a key position between upper administration and the rest of the faculty and staff within the department, all while still teaching classes. The purpose of this research study is to explore the interpersonal conflict of department chairs at public, research one universities. The research questions guiding the study are how department chairs at public, research one universities describe their lived experiences with interpersonal conflict within the university institution, and how department chairs describe their role in conflict resolution within the university institution. The methodology is narrative inquiry using qualitative data collection and narrative analysis, eliciting the stories of the participants. There were six participants, made up of three males and three females, from three different universities, in three different regions and representing varying disciplines. Each participant was interviewed three times, using 45-minute, semi-structured interviews tailored to elicit narratives and stories related to different aspects of conflict and conflict resolution. All interviews were hand-transcribed and coded using first cycle coding methods and second cycle coding methods resulting in themes including department chairs describe their experiences with conflict as being multi-directional, as reaching other departments, as “dripping down” to students, department chairs describe their role in conflict resolution as talking, listening, and asking questions, department chairs describe their role in conflict resolution as seeking input, and department chairs describe their role in conflict resolution as referring outside the department. Future research areas include expanding the study to private universities and community colleges as well as exploring individual definitions of conflict and varying conflict resolution efforts based on the conflict source.
Keywords: Conflict; Conflict resolution; Systems theory; Department chair; Systems thinking